"One for two" strategy of fully integrated textile based supercapacitor powering an ultra-sensitive pressure sensor for wearable applications. (April 2022) - Gunasekaran, Sivagaami Sundari; Veeralingam, Sushmitha; Badhulika, Sushmee
Highlights: A simple and cost-effective route was utilized to synthesize Nise2 nanoflowers on flexible carbon cloth. The fabricated NiSe2 electrode exhibited excellent half-cell specific capacitance of 980 Fg −1 at 1 Ag −1 . The flexible freestanding supercapacitor device was used powering a NiSe2 grown carbon cloth based pressure sensor for steady and reliable detection of radial pulse pressure on human wrist in real-time. Abstract: Textile-based energy storage devices help realize the full potential of flexible electronics as they combine the functionality of wearable devices with the inherent high-power density and fast charging/discharging capability of supercapacitors. In this work, Nickel di-selenide (NiSe2 ) is grown on carbon cloth (CC) via a facile one-pot hydrothermal technique and is used for supercapacitor and pressure sensor to demonstrate a textile-based fully integrated system. In a three-electrode configuration, the NiSe2 electrode produces a half-cell specific capacitance of 980 Fg −1 at 1 Ag −1, indicating its high-rate capability. Further, the NiSe2 electrode is combined with activated carbon (AC) electrodes generated from biomass to construct an asymmetric supercapacitor device (ASC) with a 1.6 V of output voltage. The ASC device delivers maximum specific energy of 50 Whkg −1 at a current density of 1 Ag −1 and a maximum specific power of 900 Wkg −1 at 10 Ag −1 . An ultra-sensitive pressure sensor is fabricated by sandwiching the NiSe2 grown carbon cloth between thin layers of PDMS, which exhibits a sensitivity of 0.91 kPa −1 in the wide dynamic pressure range of 1– 80 kPa −1 . An exceptional mechanical stability is obtained for an unloading/loading of 1 kPa of pressure for 5000 cycles. Further, it is powered using the NiSe2 /CC || AC/CC AFSC for steady and reliable detection of radial pulse pressure on the human wrist in real-time. This work paves a new path in exploring the potential of textiles when combined with nanomaterials to develop low-cost, self-powered healthcare systems for real-time monitoring of health parameters. Graphical abstract: Image, graphical abstract